Percutaneous Endoscopic Retrieval of Gizzard Foreign Body in a Goose Using an Operative Telescope - Teixeira, Pedro Paulo Maia; Pereira da Camara Barros, Felipe Farias; Bueno Borges, Luisa Pucci; Kawanami, Aline Eyko [UNESP]; Machado Silva, Marco Augusto; Werther, Karin [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP] (Univ Fed Rio Grande Do Sul, 2017)
Background: Foreign bodies are most commonly diagnosed in stomach (proventriculus and gizzard) of galliformes birds and waterfowl. Endoscopyis routinely used to assess birds' respiratory, gastrointestinal and urogenital tracts. Endosurgeryis also used for sex determination and intra-coelomaticorgan biopsy. Benefits of endoscopic approaches are widely reported in birds. Conventional surgical approaches are far more invasive and risky for those patients. Thus, the purpose of this study was to describe a successful case of gizzard foreign body removal in a greylag goose (Anseranser), using a rigid endoscopic approach through a minimally invasive percutaneous access. Case: A 2-year-old female greylag goose, weighting 3,116 g, was referred to a Veterinary Teaching Hospital presenting apathy and anorexia for at least 24 h. The results on hematologic assessment were within normal range for the species. Radiographic examination indicated presence of radiopaque content, resembling gizzard sediment. Thus, the patient undergone to endoscopy for examination and aspiration of the content. The goose was fasted for 6 h. Anesthesia was induced by face mask and maintained by endotracheal tube, using isoflurane vaporized in 100% oxygen. The patient was positionedin the lateral recumbence. The patient's neck was longer than the working length of the rigid endoscope. Thus, the telescope was inserted into the esophagus following a small distal esophagotomy, carried out on the caudal third of the neck. A 0 degrees 10-mm operative rigid telescope, with a 6-mm working channel, and a 5-mm diameter and 42-cm in length laparoscopic Babcock forceps were used. The endoscope was inserted through the esophagotomy up to the ventricle level. Sand sediments and stones were viewed. The stones were grasped and retrieved, and the sediments were rinsed with normal saline solution and aspirated with a suction cannula through the working channel of the telescope. Inspection following sediment and foreign body retrieval revealed moderate inflammation of the gizzard mucosa. Total procedure time was 24 min. The patient recovered uneventfully and was discharged following 72 h. Discussion: Rigid endoscopy provided accurate visualization of the thoracic esophagus, proventriculus and gizzard. In general, endosurgery is usually employed for sex determination in birds. It is also useful to access digestive tract using rigid endoscopy, in order to remove foreign body. Such minimally approach reduces postoperative morbidity, which is usually seen following conventional surgical approaches. This technique has been used for removal of foreign body in the digestive tract of several species. Foreign bodies found within crop should require ingluviotomy. However, could be easily removed by endoscopy. If the foreign body is within the proventriculus or gizzard, rigid endoscopy may be useful, as celiotomy could cause morbidity. The small esophagotomy access at the base of the neck was essential for the procedure. In short-necked birds, a 30 Trendelenburg positioning provides more caudal access to the digestive tract. In this case, such positioning was unnecessary. In conclusion, the use of an operative telescope provided accurate retrieval of foreign bodies and drainage of sediments within the digestive tract. Moreover, it can be used as a minimally invasive approach to foreign bodies in the esophagus, crop or stomach (esophagus and gizzard) of geese.
Keywords: Anatidae; Anseranser; digestive tract; operative telescope